STUDIES REGARDING THE RHYTHMIC GYMNASTICS FROM THE OLYMPIC GAMES - Pelin R.A (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Rhythmic Gymnastics, a symbiosis of art, aesthetic and beauty, paired with the highest performances, is a true women's sport and belongs amongst the most attractive and beautiful disciplines. The main characteristic of Rhythmic Gymnastics as a compositional discipline is the connection of the most difficult acrobatic movement elements which require a very high corporal flexibility and motor activity and which are presented by the gymnasts in perfect harmony with the music chosen for the exercise. Femininity and elegance as well as the artistic expression of the gymnasts never fail to fascinate the public.The first Olympic Games to feature Rhythmic Gymnastics as a discipline of its own were in 1984 in Los Angeles (USA). Only individual gymnasts were allowed to participate. With the exception of Romania, every eastern European country was absent. The first ever Olympic title went to Lori Fung from Canada.In 1996, Atlanta (USA) welcomed the first Group competition, in which Spain would triumph over Bulgaria and Russia.The purpose of this study is to present maximum dynamic performance of nations in the eight Olympic Games editions, since rhytmic gymnastics was included in the Olympic program.